Batch and fed-batch ethanol fermentation of cheese-whey powder with mixed cultures of different yeasts - Farkas, Csilla; Rezessy-Szabó, Judit M.; Gupta, Vijai Kumar; Bujna, Erika; Pham, Tuan M.; Pásztor-Huszár, Klára; Friedrich, László; Bhat, Rajeev; Thakur, Vijay Kumar; Nguyen, Quang D. (MDPI, 2019)
Eight yeast strains of Lachancea thermotolerans, Kluyveromyces marxianus, and Kluyveromyces waltii have been tested for their ability to ferment lactose into ethanol in mashes containing 10% (w/v) cheese whey powder (CWP). The K. marxianus NCAIM Y00963 achieved 3.5% (v/v) ethanol concentration at 96–120 h of fermentation. The ethanol production by the selected lactose-positive strains and the well-known ethanologenic Saccharomyces cerevisiae (Levuline Fb) in mixed culture was also investigated at different CWP concentrations and inoculation techniques in batch mode. The mixed culture in an equal ratio (1:1) of cell counts of K. marxianus and S. serevisiae showed an increase in lactose conversion rate. The two yeast strains in a ratio of 3:1 (three-quarters of K. marxianus and a quarter of S. cerevisiae in a total of 4.5 × 1010 cells) resulted in 72.33% efficiency of lactose bioconversion and 7.6% (v/v) ethanol production at 17.5% (w/v) of CWP concentration. In the repeated inoculation process, with the addition of three-quarter part of 3:1 ratio of mixed culture (3.3 × 1010 cells of K. marxianus) into 150 mL CWP mash at initiation and the rest quarter part (1.2 × 1010 cells of S. cerevisiae) at 24 h, 8.86% (v/v) ethanol content with 87.5% efficiency of lactose conversion was reached. Both the ethanol concentration and efficiency of bioconversion were increased to 10.34% (v/v) and 92%, respectively, by combination with fed-batch fermentation technology. Our results can serve a very good basis for the development of industrial technology for the utilization of cheese whey.
Keywords: cheese whey; bioethanol; mixed culture; fermentation; lactose conversion